Mengalihkan perhatian kepada pasar fisik aset kripto (crypto asset) - faktor predisposisi insvestor milenial kepada investasi beresiko - Akshay, F. X. John; Bertuah, Eka (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The purpose of this research is to find out the factors that influence millennial investors in shifting their intentions to the physical market of crypto assets which is growing rapidly in recent times. The method used in this research is a deductive approach to test a hypothesis. Perceived Risk, Reward Sensitivity , Knowledge become independent variables which then affect the Switching Intention.variable Personal Innovativeness is also presented as a moderating variable. The results of this study indicate that the Perceived Risk and Reward Sensitivity have an effect on Switching Intention in the Physical Crypto Asset Market so that the higher the risk perception felt by millennial investors in the financial asset market other than the crypto asset market and the higher the Reward Sensitivity they know when they decide. to invest in the physical market of crypto assets will increasingly affect their intention to participate in investing in the physical market of crypto assets. In addition, the study found a new finding that the effect of Reward Sensitivity on Switching Intention can be weakened by the moderating variable, namely Personal Innovativeness. This research has contributed to providing new Knowledge about the factors that can influence individual investors in the millennial age in Indonesia on their intention to divert their attention to investing in the physical market of crypto assets.